Comparison of tensile strength and fracture toughness under mode I and II loading of co-cured and co-bonded CFRP joints - Alessandro Pirondi; Fabrizio Moroni; Chiara Pernechele; Arturo Gaita; Luca Vescovi (Fracture and Structural Integrity)
Adhesive bonding is the elective joining system between Carbon-Fiber Reinforced Polymer (CFRP) parts because, with respect to fastening, it allows a large connection area, no additional parts (hence weight saving) and no need to drill holes into the composite, that is always detrimental for the strength due to the possibility of developing damage. However, the choice of bonding CFRP should be evaluated as alternative to direct curing in terms of strength and durability, compared to cost and manufacturing time and complexity. In this work, a comparison between co-cured and co-bonded CFRP is done with respect to tensile strength and mode I and mode II fracture toughness, in order to understand whether co-bonding guarantees the same performance of a co-cured composite part.Adhesive bonding is the elective joining system between Carbon-Fiber Reinforced Polymer (CFRP) parts because, with respect to fastening, it allows a large connection area, no additional parts (hence weight saving) and no need to drill holes into the composite, that is always detrimental for the strength due to the possibility of developing damage. However, the choice of bonding CFRP should be evaluated as alternative to direct curing in terms of strength and durability, compared to cost and manufacturing time and complexity. In this work, a comparison between co-cured and co-bonded CFRP is done with respect to tensile strength and mode I and mode II fracture toughness, in order to understand whether co-bonding guarantees the same performance of a co-cured composite part.